2018
DOI: 10.1126/science.aar6245
|View full text |Cite|
|
Sign up to set email alerts
|

CRISPR-Cas12a target binding unleashes indiscriminate single-stranded DNase activity

Abstract: CRISPR-Cas12a (Cpf1) proteins are RNA-guided enzymes that bind and cut DNA as components of bacterial adaptive immune systems. Like CRISPR-Cas9, Cas12a has been harnessed for genome editing on the basis of its ability to generate targeted, double-stranded DNA breaks. Here we show that RNA-guided DNA binding unleashes indiscriminate single-stranded DNA (ssDNA) cleavage activity by Cas12a that completely degrades ssDNA molecules. We find that target-activated, nonspecific single-stranded deoxyribonuclease (ssDNa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

79
3,396
5
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 2,942 publications
(3,486 citation statements)
references
References 42 publications
79
3,396
5
6
Order By: Relevance
“…Recently, the targeting range for Cas12a has been expanded greatly by engineered versions that recognize 5 0 -TYCV-3 0 and 5 0 -TATV-3 0 PAMs without sacrificing efficiency or specificity [71]. The latest findings about Cas12a surprisingly revealed that after target binding of either dsDNA or ssDNA Cas12a induces the indiscriminate cleavage of ssDNA in the surrounding solution [83]. In these studies it could be shown that via the CRISPR/Cas12a system targeted mutagenesis can be accomplished and that the appropriate mutations are heritable [72,73].…”
Section: Using Cas12a (Formerly Named Cpf1) In Plantsmentioning
confidence: 99%
“…Recently, the targeting range for Cas12a has been expanded greatly by engineered versions that recognize 5 0 -TYCV-3 0 and 5 0 -TATV-3 0 PAMs without sacrificing efficiency or specificity [71]. The latest findings about Cas12a surprisingly revealed that after target binding of either dsDNA or ssDNA Cas12a induces the indiscriminate cleavage of ssDNA in the surrounding solution [83]. In these studies it could be shown that via the CRISPR/Cas12a system targeted mutagenesis can be accomplished and that the appropriate mutations are heritable [72,73].…”
Section: Using Cas12a (Formerly Named Cpf1) In Plantsmentioning
confidence: 99%
“…The proposed viral detection system, named Specific High-Sensitivity Enzymatic Reporter UnLOCKing (SHER-LOCK), uses a first step of RPA (or RT-RPA for DNA), a T7 transcription step, and a Cas13a/crRNA against the virus of interest. [137,138] The advantage of these approaches is the single-molecule nucleic acid detection ability, making them a promising tool for the detection of very low-titer viruses; however, further investigation in this field is necessary. [133] The newest versions, SHER-LOCKv2 and heating unextracted diagnostic samples to obliterate nucleases (HUDSON), allows the simultaneous detection on-field of four different viruses of the same family: ZKV, Dengue virus, West Nile virus, and Yellow fever virus (all Flaviviridae, Flavivirus).…”
Section: High-throughput Sequencing (Hts) or Next-generation Sequencimentioning
confidence: 99%
“…Some enzymes simply fail to work and some choose their substrates promiscuously, necessitating thorough biochemical characterization [59][60][61][62][63][64][65] . Nevertheless, orthologous Cas9 enzymes with different PAM requirements increase targeting flexibility and allow multiplexing for combinatorial genetic screens, as demonstrated for SpCas9 and SaCas9 6,11,66 .…”
Section: Article Preprintmentioning
confidence: 99%